Empirical evidence of organizational justice and incivility in the tourism industry: Assessing the moderating role of Islamic work ethics and trust in leader. Issue 4 (1st October 2020) - Raza, Muhammad Ali; Ul-Hadi, Noor; Khan, Majid; Mujtaba, Bahaudin G.
Abstract: Organizational justice is found to act as an impetus that eventually triggers certain behaviors. As such, the purpose of this paper is to investigate the relationship among dimensions of distributive, procedural, interpersonal, and informational organizational justice with "instigated workplace incivility" (equity perspective) in the tourism industry. The study also considered the interactive roles of Islamic work ethics (IWE) and trust in the leader (TIL). Data were collected from the employees working in different hotels ( n = 363). Three dimensions of organizational justice had a statistically significant impact on IWI, while informational justice had an insignificant effect. Results also revealed that IWE and TIL do affect the hypothesized relationships. The study is a step toward understanding the importance of organizational justice in the tourism industry which can apply across transnational boundaries in the Islamic nations.